(untitled) (The Review of Diabetic Studies, 2025)
The prosthetic management of edentulous patient has been a major challenge since long. Complete maxillary and mandibular dentures have been the traditional standard of care for edentulous patients and for elderly. However, most of the patients report problems adapting to their mandibular denture due to a lack of comfort, retention, stability and inability to masticate.This is because of inadequate alveolar ridge height which occurs following resorption of bone. Implant-supported overdentures have been a common treatment for edentulous patients in the past years and predictably achieve good clinical results. Implant supported overdentures offers a practical advantage over conventional complete dentures and removable partial dentures. These include decreased bone resorption, reduced prosthesis movement, better esthetics, improved tooth position, better occlusion, increased occlusal function and maintenance of theocclusal vertical dimension. This article presents a case of the implant-retained overdenture.